IMPLEMENTASI KEBIJAKAN PENGAWASAN DALAM IZIN PENGELOLAAN AIR TANAH DI KOTA SEMARANG - Ayu Lintang Prafitri; Ari Subowo (Journal of Public Policy and Management Review, 2019)
Abstract About 80% of the clean water needs that used by the peoples derived from groundwater, especially in urban areas, industrial center, and settlement that is growing rapidly, such as Semarang City. The problems of groundwater management in Semarang City is the usage of ground water which is generally inefficient and carelessly that can be seen from the number of artesian wells from groundwater with the uncontrolled water discharge or not even registered, one of the acts from government is to manage groundwater extraction permits by Dinas ESDM Provinsi Jawa Tengah. The goals of this research is to knowing about the implementation of supervising based on the regulation, then to identifying the factors of the implementation of supervision policies in groundwater management permits at Semarang City using the Van Meter and Van Horn Theory. This research uses descriptive qualitative research method with data collecting technique through interview, observation and documentation. The result of this research is showing that Dinas ESDM Provinsi Jawa Tengah is make serious efforts to the policy, but there is some troubles for examples, weak supervision, lack of resources, lack of peoples awareness and lack of socialize leading to the conclusion that implementation of supervision policies in groundwater management permits at Semarang City is not working properly and optimally.